Research Trends in Mathematical Modeling Applied to Pandemic Cases: A Bibliometric Analysis - Rosyida, Azma; Utami, Risqi; Arlinwibowo, Janu; Fatima, Gupita Nadindra; Himayati, Ade Ima Afifa (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2023)
AbstractThe disease caused by the virus has caused a continuous pandemic worldwide since 2012. In order to slow down the rapid spread of the virus, many countries have taken recovery measures. This paper aims to analyze the trends of modeling pandemic cases in Scopus-indexed journals. The research method is a literature review using a bibliometric analysis approach starting from defining the keywords modeling' and ‘pandemic' in the Publish or Perish application with Google Scholar as the database. After narrowing the results by selecting the topic of modeling the pandemic problem it consisted of 200 articles in total. After that, the metadata was compiled using the Mendeley application, the VosViewer application was used to create a research trend visualization. The results obtained by bibliometric analysis show that the number of publications continues to increase. Which journals are published, which organizations and countries publish the most, how the evolution of perspective has changed since 2012, and which articles are most cited. We conclude that since the pandemic, there is a possibility of an evolution in the quality of publications.Keywords: bibliometric analysis; pandemic; mathematical model; Mendeley; Publish or Perish; Vosviewer. AbstrakPenyakit yang diakibatkan dari virus telah menyebabkan pandemi berkelanjutan di seluruh dunia sejak 2012. Untuk memperlambat penyebaran virus yang cepat, banyak negara telah mengambil langkah pemulihan. Tulisan ini bertujuan untuk menganalisis tren pemodelan kasus pandemi di jurnal terindeks Scopus. Metode penelitian adalah kajian pustaka dengan pendekatan analisis bibliometrik dimulai dari pendefinisian kata kunci ‘pemodelan’ dan 'pandemi' pada aplikasi Publish or Perish dengan database Google Scholar. Setelah dilakukan penyempitan hasil dengan pemilihan topik pemodelan masalah pandemi maka total artikel menjadi 200 artikel. Setelah itu dilakukan kompilasi metadata menggunakan aplikasi Mendeley, aplikasi VosViewer digunakan untuk membuat visualisasi trend penelitian. Hasil yang diperoleh dengan analisis bibliometrik menunjukkan bahwa jumlah publikasi terus meningkat. Jurnal mana yang diterbitkan, organisasi dan negara mana yang paling banyak menerbitkan, bagaimana evolusi perspektif telah berubah sejak 2012, dan artikel mana yang paling banyak dikutip. Kami menyimpulkan bahwa sejak pandemi, ada kemungkinan terjadi evolusi kualitas publikasi.Kata Kunci: analisis bibliometrik; pandemi; model matematika; Mendeley; Publish or Perish; Vosviewer. 2020MSC: 00A71, 92B05.